Ocean’s largest chlorophyll-rich tongue is extending westward (2002–2022) - Shuaixing Peng; Xiaolong Yu; Zhongping Lee; Hongyang Lin; Xin Liu; Minhan Dai; Shaoling Shang (Nature Communications)
Abstract Upwelling in the Equatorial Pacific nurtures an expansive, westward-stretching chlorophyll-rich tongue (CRT), supporting 18% of the annual global new production. Surrounding the CRT are the oligotrophic subtropical gyres to the north and south, which are suggested to be expanding under global warming. Yet, how this productive CRT has changed, expanding or contracting, remains unknown. By applying the empirical mode decomposition (EMD) method to 20-year monthly measurements of chlorophyll-a concentration from MODIS-Aqua satellite (2002-2022), we demonstrate that the CRT exhibited a significant westward extension, at an average expanding rate of 1.87 ( ± 0.82) × 105 km2/yr. The westward extension of the CRT is attributed to strengthened equatorial upwelling and a strengthened South Equatorial Current from 2002 to 2022, driven by intensified easterly trade winds as the Pacific Decadal Oscillation predominantly remains in its negative phase during this period. Interestingly, EMD analysis on central locations of the Pacific gyres suggested simultaneous extension of the gyres and the CRT during 2002-2022, with the gyres extending poleward. Our findings imply a broader cover of productive water along the equator, while its impact on tropical climate, ecosystems, and carbon cycle deserves further investigation.